Heavy metal contamination in fiddler crabs (Uca annulipes) and hermit crabs (Clibanarius sp.) in a coastal area of Northern Peninsular Malaysia - Ismail, A.; Badri, M.A.; Ramlan, M.N. (Publications Division Selper, 1991)
A preliminary study on heavy metals contamination in fiddler crabs and hermit crabs was carried out. As they are easily found in river mouth areas, they can probably serve as good indicators for heavy metals pollution. The results show Pb and Cd concentrations were high whereas Zn and Cu concentrations were within the permissible limits.